Role of surgery in management of liver abscess - Pravin Joshi Joshi (Society of Surgeons of Nepal, 2017)
Introduction: Liver abscess is a common disease in developing world. Its treatment has evolved in last few years to become less and less invasive. Percutaneous drainage of liver abscess is a wellestablished method and probably most widely accepted as well. However, large and multiloculated abscess containing thick pus may not be suitable for such methods.